Importancia De La Innovación Para Emprendedores De Micro Y Pequeñas Empresas Mexicanas Del Sector Servicio En Villahermosa-Tabasco Y Mexicali-Baja California. Estudio Cuantitativo - Jahicela Liévano; Paulina Vargas; Beatriz Pico; Juan Pérez (European Scientific Journal, ESJ, 2018)
The enterprises that result in the creation of companies are in need of implementing strategies that translate into an adequate positioning of their sector against competition. It also allows them to survive in global markets and to undergo continuous changes. For this reason, innovation as a part of the project is an important differentiating factor. In this context, this paper focuses on contrasting the actions focused on innovation by entrepreneurs of micro and small Mexican companies in the service sector of Mexicali, Baja California, and Villahermosa, Tabasco, with the aim of identifying the significant role played by innovation in the course of time. The above was achieved through a quantitative study that has a descriptive, exploratory, and correlational scope. As part of the results, it is through these strategies that it helps to promote an innovative enterprise, facilitating the generation of new ideas, and improving its ability to innovate. This would, however, results to products and services that are scalable and of greater value, taking the company to competitive levels and promoting its development in a sustainable manner. In conclusion, this effort must be permanent because there is a positive and significant relationship between innovation and actions in the development of it. This is not only for the company, but for the entity where they are located.